A View on the History of Media Theory from the Global South - Rajagopal, Arvind (Javnost-The Public, 2019)
The generalisation of “media” as a term for all forms of communication technologies occurred in part as a result of Cold War history. The implication was that every medium was in some abstract sense equivalent, whether it was print, radio or television for example. Media acquired emancipatory connotations, as if their growth would bring progress in its wake. Alongside, however, paradigms for research on media proliferated, and became increasingly hard to bridge; one outcome was the increasing marginalisation of media and communication studies from the social sciences and humanities in general, even as media scholars grew in number. This marginalization reflected a historical problem, but, interestingly, the remedies sought for it are often theoretical, drawing for example on science studies or on critical race theory. It is as if the Global South and North that have been set adrift from each other, with scholarly sanction from the academy. But for understanding the forms of contemporary globalisation, an account of Cold War media theory’s historical formation is indispensable.